Meningkatkan Kemampuan Kognitif Siswa melalui Strategi Problem Posing Di SMP Negeri 7 Padangsidimpuan - Amir, Almira (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2020)
The purpose of this study was to improve students' cognitive abilities in the implementation of the mathematics learning process by using problem posing strategies. The type of research used is Classroom Action Research (CAR) in collaboration with teachers in Mathematics. This research was conducted at Padangsidimpuan Middle School 7. With research subjects class VII-1, amounting to 28 people. Data collection instruments used were tests. CAR procedures start from the planning, action, observation and reflection stages. This research was conducted in 2 cycles, each cycle having 2 meetings. The results of this study indicate that the cognitive abilities of students of class VII-1 SMP N 7 Padangsidimpuan increased by using the Problem Posing strategy. Because the increase in students' cognitive abilities through tests given during the learning process took place from the first cycle of the first meeting from 53.57% to 57.14% the first cycle of the second meeting and the second cycle of the first meeting from 75% to 85.14% the second cycle of the second meeting . In accordance with the indicators of the action of this study the results obtained have passed the predetermined average value of the average value of 75 until the second cycle of meeting 2 which is 77.92 with the percentage of students who complete 85.72.